Genomic insight into the population history of Central Han Chinese - Xiaomin Yang; Xiao-Xun Wang; Guanglin He; Jianxin Guo; Jing Zhao; Jin Sun; Yingxiang Li; Hui-Zhen Cheng; Rong Hu; Lan-Hai Wei; Gang Chen; Chuan-Chao Wang (Taylor & Francis Group, 2021)
Background In recent decades, considerable attention has been paid to exploring the population genetic characteristics of Han Chinese, mainly documenting a north-south genetic substructure. However, the central Han Chinese have been largely underrepresented in previous studies. Aim To infer a comprehensive understanding of the homogenisation process and population history of Han Chinese. Subjects and methods We collected samples from 122 Han Chinese from seven counties of Hubei province in central China and genotyped 534,000 genome-wide SNPs. We compared Hubei Han with both ancient and present-day Eurasian populations using Principal Component Analysis, ADMIXTURE, f statistics, qpWave and qpAdm. Results We observed Hubei Han Chinese are at a genetically intermediate position on the north-south Han Chinese cline. We have not detected any significant genetic substructure in the studied groups from seven different counties. Hubei Han show significant evidence of genetic admixture deriving about 63% of ancestry from Tai-Kadai or Austronesian-speaking southern indigenous groups and 37% from Tungusic or Mongolic related northern populations. Conclusions The formation of Han Chinese has involved extensive admixture with Tai-Kadai or Austronesian-speaking populations in the south and Tungusic or Mongolic speaking populations in the north. The convenient transportation and central location of Hubei make it the key region for the homogenisation of Han Chinese.